PEAT WATER PURIFICATION USING MICROFILTRATION CERAMIC MEMBRANES BASED ON KAOLIN AND ACTIVATED CARBON - Hayu Zuhra; Alfian Putra; S Salmyah; Selvie Diana (Politeknik Negeri Lhokseumawe, 2026)
Peat water is brown in color, acidic, and contains high levels of organic matter, meaning it does not meet clean water standards. This study used kaolin-based microfiltration ceramic membranes and activated carbon for peat water purification. The membrane composition varied from kaolin (80, 85, 90, 95, 100)% and activated carbon (20, 15, 10, 5, 0)%, sintering at temperatures of 900, 950, 1000, 1050, and 1100°C to determine the effect of composition and sintering temperature on membrane characteristics and filtration performance. Characterization was performed through density, porosity, flux, surface morphology (SEM), and water filtration tests for pH, TDS, and turbidity. The best results were obtained with a membrane composed of 90% kaolin and 10% activated carbon sintered at 1100°C, with a porosity of 40.08%, density of 1.40 g/cm³, flux of 272.38 L/m²·hour, and pore size of 0.56–3.44 µm. Filtration tests showed a 94% reduction in turbidity, an increase in pH from 4.5 to 6.8, and a 41% reduction in TDS. Keywords: Ceramic Membrane, Kaolin, Microfiltration, Peat Water, Sintering